FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN SEKTOR PROPERTY DAN REAL ESTATE PERIODE 2012-222 - RAMBE, NAJIRA ULFA; KHARISMAR, EMIR (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
The purpose of this study is to empirically test and analyze the effect of profitability, company size, asset structure, capital structure, liquidity, and firm age towards firm value. In this study, objects used are corporates in property and real estate sectors from Indonesia Stock Exchange list for 11 years, period 2012-2022.This research uses quantitative research and secondary data. Sample collection method used is purposive sampling from IDX website www.idx.co.id. There were 32 companies selected as the final sample that met the criteria and obtained 352 observation data as sample. Panel data analysis method is used based on panel data testing results. Conclusions are Profitability, Firm size, Capital structure and Firm age affect firm value in corporates in sectors of property and real estate on Indonesia Stock Exchange list in 2012-2022 while Asset structure and Liquidity have no effect towards firm value in corporates in sectors of property and real estate on Indonesia Stock Exchange list in 2012-2022.